2007
DOI: 10.1002/ijc.23218
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac and its metabolites induce carcinogen metabolizing enzymes in human colon cancer cells

Abstract: Sulindac is a nonsteroidal antiinflammatory drug that has been demonstrated to be a potent chemopreventive agent against colorectal cancer in both human and animal models. In vivo, sulindac may be reversibly reduced to the active antiinflammatory compound, sulindac sulfide, or irreversibly oxidized to sulindac sulfone. Sulindac has also been shown to inhibit polycyclic aromatic hydrocarbon (PAH)-induced cancer, but the molecular mechanisms of its antitumor effect remain unclear. In this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Interestingly, it was found that AhR was a putative Wnt/ß-catenin target in prostate cancers (30). In addition, sulindac, one of the nonsteroidal anti-inflammatory drugs (NSAIDs), exerts its chemopreventive effects by inducing carcinogen metabolizing enzymes such as CYP1B1 through activating AhR (31). Therefore, aberrant expression of CYP1B1 by promoter methylation might play roles in colorectal carcinogenesis through Wnt/ß-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that AhR was a putative Wnt/ß-catenin target in prostate cancers (30). In addition, sulindac, one of the nonsteroidal anti-inflammatory drugs (NSAIDs), exerts its chemopreventive effects by inducing carcinogen metabolizing enzymes such as CYP1B1 through activating AhR (31). Therefore, aberrant expression of CYP1B1 by promoter methylation might play roles in colorectal carcinogenesis through Wnt/ß-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the S epimer is catalyzed by MsrA and as seen in Figure 6, the R epimer is reduced by an enzyme in liver that has the properties of MsrB (Brunell et al, 2011). Sulindac can also induce the P450 system and be oxidized by the P450 system to sulindac sulfone (Ciolino et al, 2008;Brunell et al, 2011). Sulindac sulfone is not an NSAID and is not a substrate for the Msr system.…”
Section: Sulindac Is a Substrate For The Msr Enzymesmentioning
confidence: 99%
“…Previous studies showed that sulindac could induce several of the P450 enzymes that were regulated by the AHR (Ciolino et al, 2006(Ciolino et al, , 2008. These authors used ethoxyresorufin as a substrate to measure induction of the P450 system but did not measure the induction of the P450 enzymes that oxidize sulindac or the effect of the sulindac FIG.…”
Section: Sulindac Metabolites Detected In Normal Ratmentioning
confidence: 99%
“…It should be noted that the R-epimer is oxidized at a faster rate than the S-epimer, regardless of which epimer is used during the preincubation (induction) period. We assume that the sulindac epimers are inducing the P450 enzymes in these experiments because Ciolino et al (2006Ciolino et al ( , 2008 have clearly shown that sulindac and its metabolites can induce several P450 enzymes. However, we should stress that we have not directly shown that the P450 enzymes are induced, only that there is an increase in P450 enzymatic activity after the cells are exposed to sulindac over a 24-h period.…”
Section: With Either (R)-or (S)-sulindac After the Pretreatment Perimentioning
confidence: 99%
See 1 more Smart Citation